Public spaces times of crisis and change (Research in urban sociology)
Urban space and public places / Ray Hutchison, Joa<U+0303>o Teixera Lopes-- Public spaces: interactions, appropriations and conflicts / Luciana Teixeira de Andrade, Luís Vicente Baptista -- Is the city unnecessary? New life spaces of young city inhabitants / Marta Smagacz-Poziemska -- Sidewalk encounters: card playing and neighborhood use in a Lisbon suburb / Joa<U+0303>o Pedro Nunes -- Sala Borsa: plural presences and innovative public spaces / Luca Daconto, Gabriele Manella -- Transformation of public space in Zagreb since 2000 / Jelena Zlatar Gamberoz<U+030c>ic, Andelina Svircic Gotovac -- Artists' studios in urban areas: a comparative study between Paris and London / Dominique Billier -- Typifying the thematic cities: study of the events organized in public spaces in the cities of Oporto, Vila Nova de Gaia and Barcelona / Fernando Manuel Rocha da Cruz -- Shaping a territory. Case study: the Moorish Quarter in Lisbon (Mouraria) / Madalena Corte-Real -- The spatial analysis of Gezi Movement in Turkey / C<U+0327>agri Eryilmaz -- Contested cityscapes: politics of vertical construction in Paris and Vienna / Andrea Glauser -- Heritage, place and neighbourhood: itineraries as public space contention in ring-road districts of Madrid / Pedro Limón López, Sergio Claudio González García -- Researching social stratification in large urban zones today / Juan José Villalón-Ogáyar -- Rethinking public spaces in waterfront areas: notes from Lisbon / Patrícia Pererira -- The earthquake and the shanty. Post-disaster social order in a Sicilian town (1908-2013) / Domenica Farinella, Pietro Saitta -- From exclusion to participation: social mediation in public housing / Micol Bronzini, Carla Moretti -- Sociological intervention as a reaction to the crisis of the city: public consultation in Warsaw / Przemyslaw Sadura, Dorota Olko